CREDIT CONGESTION ANALYSIS AT PT. SINARGA GALANG USING THE C4.5. ALGORITHM METHOD - Muhardi Saputra; Jenifer, Jenifer; Denisyah Sitorus; Situmorang, Devi Br (Sean Institute, 2022)
Credit congestion is a serious problem that is often faced by companies engaged in credit services. PT. Sinarga Galang is a company engaged in selling cars with cash or credit payment systems. The author takes data on the company's credit system in the bad category. Because the company can't analyze the credit jams that occur so it doesn't produce the right decisions in terms of filtering consumers who want to do credit. The number of bad loans, the company will go bankrupt but do not use the credit system, it will reduce sales as well and eventually can go bankrupt as well. For this reason, proper analysis is needed in classifying corporate credit bottlenecks. The method that the author uses is the C4.5 algorithm. This method is often used in research in the case of data classification because the results are precise. The results obtained in the study are a decision tree in the form of (1) if the dependents are: stuck (2) the dependents are few: stuck (3) the dependents are large: the salary is high: smooth (4) the dependents are the: moderate salary: stuck (5) the dependents are many : meager salary : smooth. These results are seen from the influence of the criteria that occur in the data, namely the number of dependents, salary / business income, monthly tenor or home ownership status. The data processing used is 100 data